If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -4 = 158 Reorder the terms: -4 + 9x = 158 Solving -4 + 9x = 158 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 9x = 158 + 4 Combine like terms: -4 + 4 = 0 0 + 9x = 158 + 4 9x = 158 + 4 Combine like terms: 158 + 4 = 162 9x = 162 Divide each side by '9'. x = 18 Simplifying x = 18
| [7x+4]+9=4 | | 0.5x-0.4x(3x+8)=0.3 | | (4)/((3x^2)-(5x^4))^4 | | 3y+2(y-4)=2 | | (11((x-7)/2)^2)-20=101 | | 15/9=8/5 | | (4)/((3x^2-5x^4)^4) | | 3x+13=90 | | ((4)/((3x^2-5x^4)^4)) | | f(x)=(4)/(3x^2-5x^4)^4 | | 9x-4=39.5 | | (4)/(3x^2-5x^4)^4 | | -10-m=-70 | | 36=(90/360)*x*x | | 4a-14=2a | | (4/5)-(2x/3)=(3/10) | | (x-3)(x+1)=x*-11 | | n^3-64/125 | | 3m-1-36=11 | | 3.16x+x= | | (X-3)(x+1)=x*11 | | 5n-7=32 | | m-39+93-13=36 | | log(22/x) | | x-.1=18000 | | 9x^2+18x-45=5 | | 54+.99x=1.54x | | 2(-1-1.5y)+3y=-2 | | -9x-5+6=-12 | | 25x(x+1)=5x+4 | | 25x^4-10x^3+1=0 | | 6a-6h+k-6w-1108=0 |